A Review on Computer Aided Detection Techniques of Oral Cancer - K. Anuradha; K. Sankaranarayanan (International Journal of Computer Sciences and Engineering, 2014)
Oral cancer is the most common cancer found in both men and women. Early Detection of Oral Cancer is important in saving life. Dental Radiographs assists experts in identifying cancers grown inside the mouth. To help radiologists, Computer Aided Detection and Computer Aided Diagnosis algorithms are developed. The algorithms help to identify cancers by reducing the need for Biopsy. This paper gives a review of Computer Aided Techniques that have been developed for detection and classification of oral cancers.